Dampak Komitmen Organisasi terhadap Kinerja Pegawai Kantor Kecamatan Siantar Utara Kota Pematangsiantar - Sudung Simatupang; Ernest Grace; Nelly Ervina; Erbin Chandra; Efendi Efendi (Universitas Batanghari Jambi, 2022)
Organizational commitment has contributed to the development of human resources in the organization whose aim is to improve the performance of the organization's employees. The purpose of this study was to determine the effect of organizational commitment on employee performance at the North Siantar District Office, Pematangsiantar City. The results of the research show that the research data have valid and reliable data results, the simple regression test shows the positive regression coefficient results from organizational commitment to performance. The partial hypothesis test shows that organizational commitment has a positive and significant effect on employee performance. Employees who have low commitment can be able to improve the performance of their employees, employees who have low commitment will produce low employee performance.